PENGGUNAAN MEDIA PEMBELAJARAN PADA MATERI TUMBUHAN SUMBER KEHIDUPAN DI BUMI KELAS IV SD BERBASIS P3 (PAPAN PUTARAN PINTAR) DENGAN SURPRISE BOX - Rosalini Zahara; Beta Rapita Silalahi; Khairiah Lubis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This development research aims to develop learning media P3 (Smart Round Board) with Surprise Box on the material "Plants that are the Source of Life on Earth" which is suitable for use in the learning process in class IV. This research was conducted in class IV of SD Negeri 105345 Sidodadi Ramunia. This development research uses the Research and Development (R&D) research method using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. However, this research only reached the development stage. The P3 media (Smart Round Board) with Surprise Box that has been developed has been validated by several experts, namely material experts, media experts and learning experts (teacher response). Based on the validation results from the material expert validator, the score was 92. From the media expert validation results, the score was 88 and from the learning expert validation results, the score was 83. So from the assessment it can be said that the P3 learning media (Smart Round Board) with Surprise Box is The material "Plants that are the Source of Life on Earth" developed is valid and very suitable for use in the learning process.